Exploring the Potential of Aquaponics Systems in Advancing Food Security in Kenya: A Scoping Review - Nicholas Outa; Ogello, Erick Ochieng; Wambui, Caroline (Science and Education Publishing, 2024)
The pressing issue of global food insecurity demands immediate attention, particularly in developing nations like Kenya. Traditional agricultural methods in these regions often involve high resource consumption, limited nutrient recycling, and substantial negative environmental impacts. In light of the escalating demand for food production and the imperative for sustainable food systems, it is crucial to explore innovative and efficient technologies capable of concurrently addressing nutrient management, water utilization, and food production challenges. The prevalent reliance on chemical fertilizers within Kenya's food production sector adversely affects both soil and environmental health, leading to a gradual decline in agricultural productivity. Additionally, many regions in Kenya grapple with water scarcity, posing a significant obstacle to food production. The heavy dependence on rain-fed agriculture further exposes food production to fluctuations in climatic conditions. Monoculture-based food systems demonstrate inefficiencies in land, water, and nutrient usage. Despite its current limited adaptability, aquaponics emerges as a promising solution to confront these challenges by optimizing water, nutrient, and land utilization in food production. Case studies in Kenya have demonstrated the potential of aquaponics in enhancing food production. This scoping review provide information on the status of aquaponics adoption in Kenya, challenges and barriers to adoption and the possible solutions to enhance adoption of aquaponics in the Kenyan food production sector.